Moringa Oleifera Seed Powder as an Alternative to Alum Powder for Water Purification - Olubiyo, Gloria Taiye; Adamu, Nefisat; Olubiyo, Comfort Kehinde; Eniola, Kehinde Imisi Temitope (FUDMA Journal of Sciences, 2026)
Clean water availability is a major issue, particularly in developing nations like Nigeria where chemical coagulants like alum render traditional treatment techniques unsuitable. The study evaluates the effectiveness of Moringa oleifera seed powder as a natural coagulant in comparison with alum powder for water purification. Specifically, it investigates the impact of varying dosages on physicochemical parameters (pH, turbidity), and microbiological quality (coliform reduction) of water sourced from Oganaji River, Ayingba, Kogi State.Moringa oleifera seed were obtained, the kernels were ground into a fine powder using a mortar and pestle and then sieved to a very fine powder. The efficacy of Moringa oleifera seed powder was verified by biochemical testing, including turbidity, jar, and pH tests. The loading doses of 0.4g/l, 0.6g/l, 0.8g/l, 1.0g/l, and 1.2g/l of the powder made from Moringa oleifera seed powder, Aluminum sulphate (alum) powder and control were used as coagulants. The best dosages for the coagulants were obtained by applying 1.2g/l of Moringa oleifera seed powder and alum powder treatments. The pH readings for alum were below the World Health Organization (WHO)'s permissible limit (acidic), whereas the pH values for Moringa oleifera seeds were between the recommended ranges. To ascertain the antibacterial efficiency, microbiological tests such total coliform counts were also carried out. Moringa oleifera seed powder is a valuable source for water purification (reducing waterborne bacterial disease) because it shows a notable decrease in coliform levels. A natural coagulant called Moringa oleifera seed powder may be a good alternative to alum powder in water treatment.
Keywords: Moringa oleifera; seed; Alum; Water; Coagulation